Administrative Factors and Key Success Factors Affecting the Surveillance, Prevention and Control of Coronavirus Disease 2019 (COVID-19) among the Health Personnel at Sub-District Health Promoting Hospital - Gerattikun Kaenphrom; Prachak Bouphan; Krissana Aunthakot; Surachai Phimha (Indian Journal of Forensic Medicine & Toxicology, 2021)
This is a cross-sectional study aimed to identifyadministrative factors and key success factors affectingthe surveillance, prevention, and control of COVID-9 among the health personnel at sub-district healthpromoting hospitals in KhonKaenProvince. The sample size was 138 health workers working in Sub-districthealth promoting hospital KhonKaenProvince, Thailand. Respondents were selected by applying systematicsampling method. A total of 905 people were selected from the study population for the quantitative studyand 12 key informants were selected for the qualitative study. The qualitative study was carried out byusing in-depth interview guidelines. The questionnaire was evaluated by 3 experts yielding an IOC value ofmore than 0.50 in all questions. The Cronbach’s alpha coefficient of the questionnaire was 0.92. Data wascollected between 21st December 2020 to 9th January 2021. Data analysis was performed by descriptivestatistics and inferential statistics as a significant level at 0.05.The results of the study showed that key success in all levels of agencies involved were with a work planto support the performance, the performance link between the hospital and link to a major hospital, and theadministrative factors of time, money, and management affecting and could jointly predict the surveillance,prevention and control of COVID-19(72.7%e (R2 = 0.727, p-value < 0.001).In conclusion, five factors areidentified to affect surveillance, control and prevention of COVID-19 amongthe public health officials.Therefore, there should be a plan to support the performance in assigning responsibilities, promotingparticipation in policy making, planning of time, budgetmanagement and regular and proper co-ordinationfor internal and external organizations.